2015
DOI: 10.1016/j.jaip.2015.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Perspective on Managing Refractory Eosinophilic Esophagitis

Abstract: Background One third of patients with eosinophilic esophagitis (EoE) do not achieve histological remission with standard medical or dietary treatment. The outcome of these patients undergoing various rescue treatments is not known and whether these patients constitute a distinct subset remains unclear. Objective To analyze EoE treatment outcomes in a predominantly pediatric population, including after initial treatment failure (rescue treatment) for differences in outcomes and clinical presentation. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 12 publications
1
25
0
2
Order By: Relevance
“…Patients' demographic data confirmed the findings reported in the literature: predominance in male sex, occurrence in both children and adults, and association between EoE and personal history of allergy, with frequent sensitization to inhalant and food allergens [11, 15, 18, 19]. With regard to incidence of refractory EoE, our data are also in line with those previously reported [16, 20], corresponding to one-third of all patients affected by EoE, at least in our pediatric population. Indeed, it was higher (57%) in our adult group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Patients' demographic data confirmed the findings reported in the literature: predominance in male sex, occurrence in both children and adults, and association between EoE and personal history of allergy, with frequent sensitization to inhalant and food allergens [11, 15, 18, 19]. With regard to incidence of refractory EoE, our data are also in line with those previously reported [16, 20], corresponding to one-third of all patients affected by EoE, at least in our pediatric population. Indeed, it was higher (57%) in our adult group.…”
Section: Discussionsupporting
confidence: 91%
“…Different approaches and combination of these treatments have been applied during the brief history of EoE, with variable results. The available data demonstrated that up to 30% of patients have a refractory disease [16]. The term refractory EoE, in fact, identifies those patients with EoE who are not responsive to therapy neither in clinical nor endoscopic or histological level.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 193 full articles were considered pertinent based on the title or abstract, and 51 were selected for inclusion: 33 articles describing therapy with topical fluticasone [2052], 17 articles describing therapy with topical budesonide [28,3234,36,44,51,5362], and 9 articles describing therapy with SFED [60,6370]. Manuscripts started in year of publication in 2003 among studies of topical fluticasone, 2007 among studies of topical budesonide, and 2006 among studies of SFED.…”
Section: Resultsmentioning
confidence: 99%
“…Very little is known about the longitudinal course of EoE patients under treatment, especially among patients on SFED, and what is known suggests relapse is common if treatments are stopped. Only two retrospective studies examined the effectiveness of second-line therapies, though at least a fifth to a third of patients fail to respond to first line therapies [34,51]. …”
Section: Discussionmentioning
confidence: 99%
“…32,22 Most importantly, it has been repeatedly demonstrated that removal of an offending food allergen or allergens results in clinical remission of EoE. [26][27][28]30,[33][34][35][36][37][38][39] There are three major approaches to dietary elimination in EoE: elemental formula, targeted elimination, and empiric elimination. 40 The goal of elimination diets is not to indefinitely limit the diets of patients to highly-restricted regimens, but to induce clinicopathologic remission, after which foods can be added back sequentially in order to identify food triggers of esophageal eosinophilia and to establish a less restrictive, long-term, therapeutic diet for effective and least restrictive disease management.…”
Section: Introductionmentioning
confidence: 99%